Projections of Sea Level Along the East Coast of North America - Love, Ryan (Université d'Ottawa / University of Ottawa, 2014)
Projections of sea level rise for the east coast of North America at 2100CE were generated considering contributions from: ocean warming, land ice melting and isostatic land motion. The primary contribution of this study is the development of an improved Glacial Isostatic Adjustment (GIA) model that includes an assessment of model uncertainty using 36 ice loading histories, 363 Earth models and a new sea level proxy database comprising over 500 sea level index points. We find that, while there are differences between our projections and the Global Mean Sea Level (GMSL) projections from the recent International Panel on Climate Change (IPCC) Assessment Report, the two sets of results agree to within uncertainty largely because some of the regional processes cancel. Our results indicate that the isostatic signal is large, contributing up to 1/4 of sea level change at 2100CE, and so must be included to generate accurate projections for this region.
Keywords: Sea Level; Projections; Glacial Isostatic Adjustment; Climate; North America; East Coast